Cystic fibrosis rabbits develop spontaneous hepatobiliary lesions and CF-associated liver disease (CFLD)-like phenotypes. Issue 1 (23rd December 2022) - Wu, Qingtian; Liang, Xiubin; Hou, Xia; Song, Zhenfeng; Bouhamdan, Mohamad; Qiu, Yining; Koike, Yui; Rajagopalan, Carthic; Wei, Hong-Guang; Jiang, Hong; Hish, Gerry; Zhang, Jifeng; et al.
Abstract: Cystic fibrosis (CF) is an autosomal recessive genetic disease affecting multiple organs. Approximately 30% CF patients develop CF-related liver disease (CFLD), which is the third most common cause of morbidity and mortality of CF. CFLD is progressive, and many of the severe forms eventually need liver transplantation. The mechanistic studies and therapeutic interventions to CFLD are unfortunately very limited. Utilizing the CRISPR/Cas9 technology, we recently generated CF rabbits by introducing mutations to the rabbit CF transmembrane conductance regulator (CFTR) gene. Here we report the liver phenotypes and mechanistic insights into the liver pathogenesis in these animals. CF rabbits develop spontaneous hepatobiliary lesions and abnormal biliary secretion accompanied with altered bile acid profiles. They exhibit nonalcoholic steatohepatitis (NASH)-like phenotypes, characterized by hepatic inflammation, steatosis, and fibrosis, as well as altered lipid profiles and diminished glycogen storage. Mechanistically, our data reveal that multiple stress-induced metabolic regulators involved in hepatic lipid homeostasis were up-regulated in the livers of CF-rabbits, and that endoplasmic reticulum (ER) stress response mediated through IRE1α-XBP1 axis as well as NF-κB- and JNK-mediated inflammatory responses prevail in CF rabbit livers. These findings show that CF rabbits manifest many CFLD-like phenotypes and suggest targeting hepatic ER stress and inflammatory pathways for potential CFLD treatment.